Antara Toleransi Dan Sinkretisme: Telaah Kritis Terhadap Pluralisme Dalam Kehidupan Sosial Dan Keagamaan Pada Masyarakat Indonesia Yang Majemuk - Thio Donald Sugiarto (Sekolah Tinggi Teologi Bethel Ambon, 2026)
Pluralism is one of the most widely discussed concepts in contemporary social and religious studies. However, debates surrounding pluralism are often marked by conceptual ambiguity because social pluralism and religious pluralism are frequently treated as identical concepts. This situation gives rise to two equally problematic tendencies: syncretism, which obscures religious identity, and intolerance, which fosters hostility toward differences. Therefore, examining the boundaries of pluralism is essential within pluralistic societies that seek to preserve social harmony without compromising the integrity of religious convictions. This article is based on the thesis that social pluralism constitutes an important foundation for communal life, whereas religious pluralism, when developed into theological relativism, has the potential to blur religious identity and encourage syncretism. This study employs a qualitative approach using library research. Data were gathered from literature in the fields of sociology of religion, philosophy of religion, theology of religions, human rights, and religious freedom, and were analyzed through descriptive and critical approaches. The findings indicate that social pluralism contributes positively to democratic life, respect for human dignity, and cooperation across social identities. In contrast, religious pluralism faces conceptual difficulties when fundamental differences among religions are reduced to expressions that are assumed to be equally valid responses to the same reality. At the same time, the preservation of religious identity must not develop into intolerance. This article proposes a new concept, namely coexistence without relativism, as a model that rejects two opposing extremes: syncretism, which erases identity, and intolerance, which is hostile toward difference. This model enables respect for diversity while simultaneously preserving the integrity of each religious community’s beliefs.